2010
DOI: 10.1103/physreva.81.062130
|View full text |Cite
|
Sign up to set email alerts
|

Sudden change in quantum and classical correlations and the Unruh effect

Abstract: We use the Unruh effect to analyze the dynamics of classical and quantum correlations for a two-qubit system when one of them is uniformly accelerated for a finite amount of proper time. We show that the quantum correlation is completely destroyed in the limit of infinite acceleration, while the classical one remains nonzero. In particular, we show that such correlations exhibit the so-called sudden-change behavior as a function of acceleration. Eventually, we discuss how our results can be interpreted when th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 57 publications
2
85
1
Order By: Relevance
“…The same is true for MID which stays very close to the maximal value of M = 1. (Céleri et al, 2010) consider the case of entangled detectors coupled to a scalar field which acts as a thermal bath. To achieve a more realistic scenario, the detector is switched on for a finite time.…”
Section: Klein-gordon Fieldsmentioning
confidence: 99%
“…The same is true for MID which stays very close to the maximal value of M = 1. (Céleri et al, 2010) consider the case of entangled detectors coupled to a scalar field which acts as a thermal bath. To achieve a more realistic scenario, the detector is switched on for a finite time.…”
Section: Klein-gordon Fieldsmentioning
confidence: 99%
“…Moreover, there exist intimations that the QD is the resource responsible for the speed up in deterministic quantum computation with one quantum bit [11,12]. Entanglement and QD have been studied extensively in a number of contexts, e.g., low dimensional spin models [13][14][15][16][17][18][19], open quantum systems [20][21][22][23][24], biological [25], and relativistic [26,27] systems. Recently, pairwise QD and entanglement have been analyzed as a function of distance between spins in the transverse field XY chain for both zero and finite temperatures cases [18,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the QD and entanglement show very different dynamical behaviors and the QD is more robust to decoherence. Recently, an interesting dynamical behavior of correlations, named sudden transition, has been observed [23,24]. It shows that under certain initial states the correlation undergoes sudden change between a "classical decoherence" phase and a "quantum decoherence" phase [22,23].…”
mentioning
confidence: 99%
“…Motivated by these considerations, we here study the correlation dynamics for various bi-partitions of a composite system consisting of two qubits A and B, and two local environments E A and E B . In contrast to previous investigations [20][21][22][23][24][25][26], we here assume that E A and E B are non-identical. We find that, contrary to what is usually stated in the literatures [26,30], the transfer direction of either the entanglement or other quantum correlations can be controlled by combining different noisy environments.…”
mentioning
confidence: 99%